Problematika Penyelenggaraan Pendidikan Widyalaya di Provinsi Bali - I Nyoman Ariyoga; I Made Bagus Andi Purnomo (Jayapangus Press, 2026)
The implementation of widyalaya education in Bali Province continues to face various challenges related to regulatory implementation, institutional governance, limited human resources, and insufficient support from stakeholders and local governments. These conditions indicate a gap between the policy demands of Hindu religious education and the actual practices of educational management in the field. This study aims to analyze the problems in the implementation of widyalaya education, particularly concerning regulatory adaptation, institutional management, the availability of educators, learning facilities, and external support for the sustainability of widyalaya institutions in Bali Province. This research employed a qualitative method with a case study approach. Data were collected through observations, in-depth interviews, focus group discussions (FGDs), and document studies involving principals, teachers, foundations, and stakeholders in Hindu education. The findings reveal that widyalaya institutions still encounter several significant obstacles, including unpreparedness in adapting to Minister of Religious Affairs Regulation Number 2 of 2024, limited educational personnel, low digital literacy, inadequate teaching materials and learning media, and suboptimal support from local governments in strengthening infrastructure, funding, and educational governance. The study demonstrates that the challenges faced by widyalaya are not merely internal institutional issues, but are also closely related to regional education policies and the broader support system for Hindu religious education in Indonesia. This research implies the importance of strengthening collaborative policies, improving human resource capacity, and developing data-based educational governance to support the sustainability of widyalaya as adaptive and high-quality Hindu educational institutions.